História natural, biogeografia e a genética de populações de Partamona rustica, uma abelha endêmica de florestas secas do Brasil - Miranda, Elder Assis (Universidade Federal de São Carlos, 2016)
Partamona rustica is a stingless bee endemic to dry forests in Brazil. Despite its importance as a pollinator and its occurrence in endangered areas, such as the Caatinga (scrubland forest) and Cerrado (savanna) biomes, its natural history, biogeography, population genetics and evolutionary history are poorly known. This PhD Dissertation is presented in four chapters addressing specific aims to reduce the gaps in knowledge regarding P. rustica. In Chapter I, aspects of the natural history of this bee were investigated. The results revealed that P. rustica occurs from the northern portion of the state of Minas Gerais to the southern portion of the state of Bahia in the Caatinga and Cerrado biomes, contouring the plateaus and hills of Chapada Diamantina by the east. It is a floral visitor of at least 62 kinds of plant and its nests are built in arboreal termite nests constructed by Constrictotermes cyphergaster. In Chapter II, the hypothesis was tested that populations of stingless bees, such as P. rustica and Partamona helleri, have a high degree of differentiation when analyzed for mitochondrial genes due to the fact that the occupation of a site is performed by a small number of founding females. Therefore, each occupation event may exhibit a founder effect. The results revealed few haplotypes per population as well as a high degree of genetic differentiation, which supports the hypothesis. Implications for future studies were also indicated, such as the need to change the current focus of studies related to the genetic structure of bee populations, which usually estimate the degree of inter-population differentiation, to x estimates of genetic relatedness among queens, workers and males who founded the colonies of a given population. In Chapter III, the genetic relatedness among workers of P. rustica was estimated to evaluate the role of males in dispersal and gene flow among colonies and populations. The results revealed a low degree of average genetic relatedness among workers of colonies from the same locality and even lower relatedness among workers of colonies from different localities, suggesting that, although the areas analyzed were occupied by few females, dispersal promoted by males reduces relatedness and, consequently, the risk of inbreeding, which is harmful to hymenopterans due to their complementary sex determination system (locus csd). In Chapter IV, we used an integrative approach to reconstruct the evolutionary history of P. rustica in a spatiotemporal framework. The results identified two groups: one to the west and the other to the east of the São Francisco River Valley, which putatively diverged during the late Pleistocene, and indicated the western group as ancestral to the eastern group. The results also indicate that the inferences from both the analysis of genetic data and spatial distribution modelling are compatible with a history of populations of a constant size. The data presented in this thesis can be used to guide conservation and management strategies concerning the species as well as the Caatinga and Cerrado biomes, broaden knowledge on the biology and genetics of stingless bees, which can be useful in beekeeping and bee management, as well as reinforce the need for more detailed investigations into Pleistocene climate changes and the effects on the diversification of the endemic biota in Neotropical dry forests, especially studies involving the considerable diversity of bees in this region.
Natural history, biogeography and population genetics of Partamona rustica, an endemic stingless bee from dry forests in Brazil
Keywords: Abelhas sem ferrão; Filogeografia; Florestas secas; Genética de populações; Genética familiar; CIENCIAS BIOLOGICAS::GENETICA